TRADITIONAL VS. MODERN EDUCATION SYSTEMS - Ko`shkinova Aynash Garifulla Qizi; Khamitov Eldorbek Erkinovich (TADQIQOTLAR, 2026)
ABSTRACT:  The  comparison  between  traditional  and  modern  education systems remains a central issue in contemporary educational research. As societies evolve and the demands placed on learners increase, education systems must adapt to prepare  students  for  academic,  professional,  and  social  challenges.  This  article provides a comprehensive comparison of traditional and modern education systems by examining their philosophical foundations, teaching methods, roles of teachers and learners, and overall impact on learning outcomes. Based on an analytical review of academic literature, the study highlights the strengths and limitations of both systems and  argues  that  an  integrated  approach  may  offer  the  most  effective  solution  for improving educational quality in the modern world.